Pengaruh Antara Terapi Mindfulness dengan Tingkat Kecemasan pada Mahasiswa Keperawatan Tingkat Akhir di STIKes X - Arini, Larasuci; Silvia Dora, Mechi; Sari Ramadani, Fatimah; Syarli, Setiadi (Pustaka Galeri Mandiri, 2026)
Based on data from the World Health Organization (WHO), 450 million people globally suffer from anxiety-related health issues. Young adults account for 150 million of these individuals, and 57% of the total population experiences work-related anxiety during their studies. The prevalence of anxiety in Asia is 65 million young adults with anxiety issues during their undergraduate studies, with final-year students being the most affected. A preliminary study conducted through interviews with eight final-year nursing students at STIKes X revealed that five of them experienced anxiety while facing their thesis.This research aimed to determine the effect of mindfulness therapy on the anxiety levels of final-year nursing students writing their thesis at STIKes X. The study used a This research aimed to determine the effect of mindfulness therapy on the anxiety levels of final-year nursing students writing their thesis at STIKes X. The study used a Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed using a paired sample t-test.The study, conducted from July 10, 2025, at STIKes X, found a p-value of 0.001 (< 0.05). This indicates that there was a significant effect of mindfulness therapy in reducing anxiety levels among final-year nursing students. The conclusion is that mindfulness therapy can be an effective method to decrease anxiety for students, particularly those working on their thesis, and future researchers are encouraged to explore other non-pharmacological therapies to address anxiety